Emerging immunotherapeutic strategies for malignant serous effusions: current evidence and future directions - He, Weimin; He, Xia; Qiao, Zhi; Wang, Yongsheng (Frontiers in Oncology, 2026)
The invasion of serous cavities by malignant tumors, leading to implantation metastasis, is a hallmark of advanced cancer, causing pathological buildup of fluid (malignant effusions) containing cancerous cells, which indicates advanced disease and poor prognosis. The primary cancers involved include lung, breast, gastric, and ovarian cancers, affecting a large patient population with a high incidence rate. Because effective treatment options are limited in clinical practice, patients with malignant effusion, based on the severity, typically survive only 3 to 15 months. Traditional therapies, such as local drainage combined with intrapleural chemotherapy, have limited efficacy and tolerability. Immunotherapy has emerged as a potential approach for drug-resistant malignant tumors, driven by deeper insights into resistance mechanisms, tumor heterogeneity, and the immune microenvironment of malignant effusions. Preclinical studies show that liposomal nanoparticles containing cyclic dinucleotides (LNP-CDN) can activate the STING (Stimulator of Interferon Genes) signaling pathway; local injection into mouse pleural cavities enhances the “cold” tumor immune response and improves tumor treatment outcomes. In early-phase clinical studies and small cohorts, local infusion of chimeric antigen receptor T cells (CAR-T) showed preliminary survival benefits over first-line standard treatments, with good safety profiles and high tolerable doses, but these findings require further validation in large-scale trials. This article reviews tumor serosal metastasis epidemiology, summarizes current treatment options, and discusses the development direction of clinical strategies considering the immune microenvironment of malignant effusions, with a focus on advancements in cell immunotherapy. Despite the therapeutic potential of immunotherapy, its efficacy in malignant effusions, while measurable, remains to be fully optimized. A key limitation is that most evidence presented derives from preclinical models, small patient cohorts, or phase I/II trials, and definitive clinical efficacy remains unconfirmed.